How storytelling impacts students in their psychotherapy training - Dempsey, Karen (European Journal for Qualitative Research in Psychotherapy, 2023)
The use and impact of storytelling in counselling and psychotherapy training was explored using a mixed-methods approach. An online survey completed by 30 therapists and 12 counselling tutors produced both quantitative and qualitative data. The latter were analysed using Reflexive Thematic Analysis (RTA). Therapists and tutors all agreed that the use of story was important, or extremely important, in the training room. Case studies and clinical anecdotes were the type of story preferred by a majority of learners. Four themes were created from the RTA process. The first was story for Making Meaning, in worldly, personal, and universal ways. The second was Activating Learning, where story brought theory to life, helped concepts make sense, and embedded learning. The third theme was I Will Survive, where clinical and personal stories from a tutor demonstrated how a practitioner could struggle and overcome mistakes. The fourth theme was Quality of Presence, where the tutor-student relationship emerged as a vital component in modelling the skills, attitude and presence required to be a therapist.